Ecological risk assessment of Ervedosa mine (Portugal): Tier 1—Screening evaluation of soil ecotoxicity - Gonçalves, F. (2019)
This study was carried out in the Ervedosa mine area (NE Portugal), where underground and open pit exploration of tin and arsenic minerals was performed in the past. Environmental contamination makes it essential to carry out an ecological risk assessment (ERA) to assess the toxic potential of soil and water in the surrounding area. Bearing this in mind, the aim of this work was to make an initial screening to evaluate potential impacts of contamination in soil samples from the area. The screening step of ERA tier1) was carried out in 16 sites distributed along four transects(C, D, E, F) and a reference site. A battery of bioassays was conducted for: (i) elutriate soil samples aimed in evaluating their potential to cause immobilization of Daphnia magna, growth inhibition of Pseudokirchneriella subcapitata and Lemna minor, and bioluminescence reduction in Vibrio ﬁscheri and (ii) soil samples evaluating avoidance behavior with Eisenia andrei and Folsomia candida and emergence of Zea mays. Soil elutriates from all transects–except C– were toxic to all aquatic organisms. Elutriates from F were the most concerning ones, with almost all samples causing acute toxicity. Avoidance behavior of E. Andrei was highly signiﬁcant for almost all soil samples, while F. candida avoidance was less sensitive and discriminatory. Seed emergence in Z. mays was signiﬁcantly reduced in F1 (0%). Results show that the areas subjected to deposition of residual wastes are highly toxic and support the decision to proceed to tier 2 of ecological risk assessment.